SENI PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Marzuki, Idelia; Wahyudi, Apri (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2019)
AbstractLearning mathematics is an artistic value. But it will be a lesson in the "specter" category for some students when math teachers are able to apply fun learning strategies. Need concern for students and carefulness of their abilities with high detail. In the learning process and mathematics learning outcomes students are not only determined by the school, the pattern of the structure and contents of the curriculum, but most are determined by the ability of teachers who teach and guide learning that is effective, fun and will be better able to manage their classes so that student learning is at a level optimal. The teacher must have the courage to change and perfect himself with the demands of a continuous era, besides that he must dare to examine the shortcomings in all aspects in carrying out their duties, able to provide opportunities for learning in children as broad as possible and willingness to perfect various aspects of education. Learning mathematics can be an art when the teacher starts a lesson by arousing student motivation, so students can concentrate at the beginning of the meeting, and can receive the material delivered by a teacher well. Ending a lesson with special, so students always miss the next meeting.